2016
DOI: 10.1007/s00484-015-1130-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of heat waves on nonaccidental deaths in Jinan, China, and associated risk factors

Abstract: An ecological study and a case-crossover analysis were conducted to evaluate the impact of heat waves on nonaccidental deaths, and to identify contributing factors of population vulnerability to heat-related deaths in Jinan, China. Daily death data and meteorological data were collected for summer months (June to August) of 2012-2013. Excess mortality was calculated and multivariate linear regression models were used to assess the increased risk of heat waves on deaths. Univariate and multivariate logistic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…It affects human health, reduces labor capacity and productivity of exposed workers, damages infrastructures, and decreases crop yields (Steffen et al, 2014). For example, heat waves are associated with excess deaths in many Chinese cities (Gao et al, 2015;Ma et al, 2015;Zhang et al, 2016). Mortality increases shortly after temperature exceeds a certain level (Gao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It affects human health, reduces labor capacity and productivity of exposed workers, damages infrastructures, and decreases crop yields (Steffen et al, 2014). For example, heat waves are associated with excess deaths in many Chinese cities (Gao et al, 2015;Ma et al, 2015;Zhang et al, 2016). Mortality increases shortly after temperature exceeds a certain level (Gao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“… 15 Our previous study in Jinan found that heat waves significantly increased the risk of mortality and caused 24.88% excess non-accidental deaths. 17 This study used more recent data to investigate the effect of both heat waves and cold spells on the daily number of deaths in Jinan. Furthermore, we have explored the effect of temperature extremes on vulnerable populations.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, extremely high temperature in Guangzhou was linked with an increase in the risk of death [ 8 ]. Elderly, women, and individuals with pre-existing diseases are considered to be very vulnerable to heat-related illnesses in China [ 9 , 10 ]. Therefore, more attention should be paid to the health effects of heat and heat waves.…”
Section: Introductionmentioning
confidence: 99%